1999
DOI: 10.1007/bf02466547
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of the structure of a high-temperature nickel alloy fabricated by two different technologies

Abstract: High-temperature treatment of the melt (HTTM) is a very simple and available technique for stabilizing and improving the service properties of parts. It consists in heating the melt to a certain critical temperature, a hold, and cooling. The present paper is devoted to the effect of HTTM, the standard heat treatment, and long isothemaa] holds at the service temperatures on the structure and properties of castable high-temperature nickel alloy ZhS6U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Therefore, it is believed that the solidification microstructure variation for the elevated superheating temperature cannot be owing to the external solidification parameter but should be attributed to the internal melt characteristic change. It has been found that Ni 3 Al-like cluster, residual MC carbide and other highmelting particle still exist in the Ni-based superalloy melt near the liquidus [8][9][10][11][12][13][14]. With the melt temperature increase, those clusters will decrease in their sizes and even disappear, which leads to the increase of composition uniformity.…”
Section: As-cast Microstructurementioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, it is believed that the solidification microstructure variation for the elevated superheating temperature cannot be owing to the external solidification parameter but should be attributed to the internal melt characteristic change. It has been found that Ni 3 Al-like cluster, residual MC carbide and other highmelting particle still exist in the Ni-based superalloy melt near the liquidus [8][9][10][11][12][13][14]. With the melt temperature increase, those clusters will decrease in their sizes and even disappear, which leads to the increase of composition uniformity.…”
Section: As-cast Microstructurementioning
confidence: 91%
“…With the melt temperature increase, those clusters will decrease in their sizes and even disappear, which leads to the increase of composition uniformity. The melt at this kind of equilibrium or near equilibrium state has increased supercooling degree and compressed temperature range for crystallization [10][11][12][13][14]. It is very important that due to the so-called "heredity effect", the melt will remain its high temperature characteristic to a certain extent even when it is cooled down [3][4][5][7][8][9][10][11][12][13][14].…”
Section: As-cast Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…Характерные точки перегибов и угол наклона участка с интенсивными убыванием σ зависят от структурных изменений, происходящих в сплавах в период испытаний. Наши исследования [12,13] и результаты других ученых [14 -21] позволяют представить общий порядок этих структурных изменений: после литья и термической обработки структура монокристаллических ЖНС состоит из γ-никелевой матрицы, основной упрочняющей мелкодисперсной γʹ-вторичной фазы и эвтектики (γ + γʹ). Температура и приложенные во время испытаний нагрузки приводят к существенным структурным изменениям: образуется рафт-струкутра и возникают дислокации; кубоидные выделения основной упрочняющей фазы коагулируют, происходит рост их блоков; при выдержках свыше 1100°С количество γʹ-вторичной фазы существенно снижается; округлые выделения γ + γʹ эвтектики заменяются на колонии мелких частиц; структурные изменения приводят к возникновению и росту охрупчивающих топологически плотно упакованных фаз, типа µ, σ, Лавеса и других.…”
Section: методикаunclassified